2012
DOI: 10.1007/s00520-012-1606-5
|View full text |Cite
|
Sign up to set email alerts
|

Music interventions for psychological and physical outcomes in cancer: a systematic review and meta-analysis

Abstract: Individual randomized trials suggest that music intervention is accepted by patients and associated with improved psychological outcomes. The effects of music on vital signs especially blood pressure are small. High-quality trials are needed to further determine the effects of music intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
67
0
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 35 publications
6
67
0
9
Order By: Relevance
“…Music was shown to decrease heart rate in cancer patients (z = 2.32) (Zhang et al, 2012) and non-cancer patients (standard mean difference of -2.63) (Loomba et al, 2012) but not older adults during exercise routines (z = 0.80) (Clark et al, 2012). In a meta-analysis, Zhang et al (2012) found that recorded music had a large effect across studies on the decrease of respiratory rates in cancer patients (z = 5.16).…”
Section: Music Therapymentioning
confidence: 98%
See 2 more Smart Citations
“…Music was shown to decrease heart rate in cancer patients (z = 2.32) (Zhang et al, 2012) and non-cancer patients (standard mean difference of -2.63) (Loomba et al, 2012) but not older adults during exercise routines (z = 0.80) (Clark et al, 2012). In a meta-analysis, Zhang et al (2012) found that recorded music had a large effect across studies on the decrease of respiratory rates in cancer patients (z = 5.16).…”
Section: Music Therapymentioning
confidence: 98%
“…Populations represented in music therapy physical rehabilitation studies have included premature infants (Standley, 2002), cancer patients (Zhang et al, 2012), diagnosis-non-specific patients (Loomba, Shah, Chandrasekar, Arora, & Molnar, 2012;Pelletier, 2004), older adults (Clark, Taylor, & Baker, 2012), epilepsy patients (Dastgheib, et al, 2013), mental disorder patients (Gold, Solli, Kruger, & Lie, 2009;Gold, Voracek, & Wigram;Silverman, 2003) Pedersen, & Bonde, 2002). One meta-analysis indicated positive effects for all physical rehabilitation patients in terms of behavior reinforcement (Standley, 1996).…”
Section: Music Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Seven high quality randomized controlled studies indicated the music therapy significantly reduces the anxiety levels of patients measured by Self-Rating Anxiety Scale. Two moderate quality randomized controlled studies which used Hamilton Anxiety Scale and eight moderate quality randomized studies which was used State-Trait Anxiety Inventory found that music therapy affect positively the patients anxiety (Zhang, Wang, Yao, Zhao, Davis, Walsh, & Yue , 2012). Although systematic review indicated that the music therapy significantly decreases the anxiety and pain level in the perioperative settings (Nilsson, 2008), some researchers found different results.…”
Section: The Effects Of Music Therapy On Psychological and Physiologimentioning
confidence: 99%
“…Although, the effects of music on pain and anxiety were researched, only a few studies had high quality methodology (Zhang, et al, 2012). Also, there is not any common methodology in the music therapy research and researchers suggested that children's symptoms should be measured pre, during, and after the treatment to evaluate the effectiveness of the music (Chen, et al, 2013).…”
Section: The Aims Of the Present Research And Hypothesesmentioning
confidence: 99%